USE OF PRELACTEAL FEEDS- STUDY IN TRADITION: Prelacteal Feeds - Pirzada, Saima; Anwar, Zahid; Gul, Rafia; Iqbal, Nazia; Noor, Fatimah (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find the types and frequency of prelacteal use, factors influencing their use and its impact on breastfeeding.Study Design: Cross-sectional study.Place and Duration of Study: Fatima Memorial Hospital, Lahore, Pakistan from Jul to Dec 2019.Methodology: In the study, mothers and female attendants of newborn babies were interviewed following a specific questionnaire. The given answers were recorded and captured data about socio-demographics, knowledge, attitude and actual practices of mothers and families related to use of prelacteals. The results were analysed using SPSS 22.Results: We interviewed 1601 mothers and female attendants of neonates. The mean age was 32.3 ± 8.2 years. Most of the females were married (1211, 75.6%) and resided in Lahore (1281, 80%). About one third, 581 (36.3%) were either illiterate or had inadequate schooling. Two-thirds (1000, 62.5%) of women wanted to give some prelacteal feed soon after birth. Honey was the most the commonest choice (in 722, 45.1%), seconded by ghutti (107, 6.7%). Most females (1467, 91.6%) wanted to give colostrum, and 1552 (96.9%) would breastfeed the baby. 1221 (75.2%) wanted to start mother-feed immediately or within 2 hours of birth.Conclusion: The use of prelacteal is common in Pakistan culture. A consistent effort is needed to counter the unsafe prelacteal use.